PENGARUH RASIO BUBUK KOPI DENGAN AIR DAN SUHU PADA METODE COLD BREW TERHADAP KARAKTERISTIK MINUMAN KOPI ARABIKA - Larasati, Tia; Putra, Gusti Putu Ganda; Suhendra, Lutfi (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 10 No 1 (2023): Scientific Journal of Food Technology (Maret)DO - 10.24843/MITP.2023.v10.i01.p24, 2023)
Cold brew coffee drinks are prepared at low temperatures for a longer time than traditional hot extraction methods and extraction times range from 8-24 hours. This study aims to determine the effect of the ratio of coffee grounds to water and temperature in the cold brew method on the characteristics of arabica coffee drinks, determine the right combination of treatments, and determine the stability of caffeine levels, pH, total phenol and taste in arabica coffee drinks. This research consists of two stages, namely Stage 1 determining the ratio of coffee grounds to water and temperature using the cold brew method. Phase 1 research used a Randomized Block Design. The independent variables used are two factors, namely factor A consisting of 3 levels, namely the ratio of coffee powder to water 1:10, 1:15, and 1:20. Factor B is immersion in cold water at 5 O C, 15 O C, and 25 O C. The study was repeated 2 times to obtain 18 experimental units. The parameters observed in the first stage of the study were the pH value, total phenol, and caffeine content as well as the characteristics of aroma, taste, acidity, body, and aftertaste. Determination of the best treatment is done by sensory test using panelists (limited taster). Phase 2 research is the stability test of the best Arabica coffee drink during storage. The design used is a simple correlation analysis, to determine the relationship between storage time and the stability of Arabica coffee drinks, for 7 days with a storage temperature of 5 O C. The results of this study showed that the ratio of coffee powder to water and soaking temperature significantly affected the chemical characteristics of pH, total phenol, and caffeine content as well as the characteristics of aroma, taste, acidity, body, and aftertaste in Arabica coffee drinks. The best Arabica coffee drink with the cold brew method got the highest score of 7,15, in the treatment of the ratio of coffee powder to water 1:10 and a temperature of 25 O C. With chemical characteristics pH 5,08, total phenol 2,128 g GAE/100ml and caffeine content 128,207 mg/100ml and taste characteristics on aroma preference an average score of 8, taste preference average score of 7,5, acidity preference average score an average of 4,5, an average score of 8 for body preference and an average aftertaste score of 7,75. The stability of Arabica coffee drinks using the cold brew method at a storage temperature of 5 O C revealed a negative correlation between storage time and the stability of the chemical characteristics of pH value, total phenol and caffeine content, and taste characteristics, except for taste preferences where the resulting correlation was positive correlation.